Identification of linear B-cell epitopes of Senecavirus A VP2 protein using monoclonal antibodies - Jiang, Yao; Guo, Zhenhua; Weng, Maoyang; Chen, Linlin; Li, Qingmei; Zhang, Lei; Qiao, Songlin; Zhang, Gaiping (Frontiers in Microbiology, 2025)
IntroductionSenecavirus A (SVA) is an emerging vesicular pathogen in swine with clinical signs similar to those of foot-and-mouth disease, porcine vesicular disease and vesicular stomatitis, making the control of swine vesicular disease outbreaks difficult. Therefore, the development of effective diagnostics and vaccines for SVA has become critical. VP2 is a structural protein that elicits a strong immune response, which positions it a candidate for diagnostic and vaccine development.MethodsIn this study, five high-titer monoclonal antibodies (mAbs) were produced using hybridoma technology. Twenty-eight peptides covering the entire VP2 sequence were synthesised by overlapping peptide synthesis, and the positive peptides were screened with the five mAbs by ELISA and Dot-blotting. The peptides were then further truncated to identify the minimal epitope regions based on immunoinformatics analyses.ResultsFour mAbs were identified that reacted with peptide 15 and one mAb reacted with peptide 26. Further truncation of these peptides led to the identification of two novel minimal epitopes: 156-NEEQWV-161 and 262-VRPTSPYFN-270. Structural and sequence alignment analyses revealed that epitope 156-NEEQWV-161 is located in the flex-loop region of the VP2, whereas epitope 262-VRPTSPYFN-270 is located in the β-sheet of the VP2. Both epitopes were highly conserved among typical SVA isolates from different countries.DiscussionThis study identifies two novel B-cell epitopes on the VP2, contributing to the development of VP2-based diagnostic tools with clinical applications. The findings also provide valuable material for the design of novel vaccines against SVA, offering new insights into the immune response to this pathogen.